Análisis de rotación del personal externo del grupo Éxito. (2017)
The Grupo Éxito provides to the students of the Faculty of Economic Sciences, Administrative and Management and Allied of the UCC the opportunity to do professional practices in their facilities; through this experience and with a weekly follow-up made from the position of practitioner Administration and Human Resources Support (Outsourcing), it was analyzed the performance of staff of external support. It is as well as the overall objective of the present work, it was to implement a process of monitoring and analysis of external staff of the Grupo Éxito linked through temporary agencies, in this way it was identified that the company with a long history has developed a remarkable structural, commercial and/or services growth in the whole country (Colombia), it is for this reason that requires a ample staff with various hierarchical levels and to satisfy the needs of the different warehouses should resort to outsourcing system, this system conformed in the Grupo Éxito by temporary Jiro S.A, Manpower Group, Multiempleos S.A, Extras S.A, Eficacia S.A, Gente estratégica, Gente Caribe y Yod buen servicio, it is a system that in Colombia is of great use to offer an efficient alternative staffing companies. The Grupo Éxito uses this system throughout the year and especially in periods of high commercial activity, however, and despite of supplying vacancies, these employees and also the companies that offer the service presented certain problems that in one way or another affect the good service of the Almacenes Éxito and produce a high labor desertion. Compared to what this identified the primary reasons of abandonment of work and its time it was possible to establish strategies to solve the problems as perform inductions. In relation to the present, it identified the primary reasons of abandonment of work and at the time it was possible to establish strategies to solve the problems, as make inductions, recruit staff close to the establishment and create a basic operation manual, this allowed provide adjustments to outsourcing processes in the Grupo Éxitos and in turn improve results.